Drying kinetics of pepper in swirling fluidized bed dryer - Haron, Nazrul Syaif (2019)
Malaysia is one of the pepper producing nation with exports reaching more than 90,000 tonnes between 2010 until 2016. Pepper requires drying before and traditionally sun drying is the favourite technique due to low-cost feature. However, the recent climate change has affected the sun drying which is heavily dependent on weather conditions. This study proposes the swirling fluidized bed dryer (SFBD) as an alternative technique for pepper drying. A lab scale SFBD was used to investigate the bed’s hydrodynamics and drying characteristic. Batch experiments were carried out for three bed loadings of 1.0 kg, 1.4 kg & 1.8 kg at a five drying temperature of 50 °C, 60°C, 70°C, 80°C and 90°C. From the hydrodynamics study, the SFBD exhibited excellent particle mixing with relatively low bed pressure drop. Four regimes of operation were discovered namely the packed regime, minimum fluidization, minimum swirling and swirling regime. As for the drying studies, lower bed loadings and higher drying temperatures result in higher moisture removal rate. The drying curves plotted indicate that the constant rate drying period was insignificant and thus drying of pepper in SFBD can be assumed to be in falling-rate period for all bed loadings and drying temperatures. A total of six thin-layer models were chosen from the literature to model the drying kinetics of pepper and it was found that Logarithmic model provided the best fit for the present drying condition with coefficient of determination, R² = 0.9990807, root mean square error, RMSE = 0.0105431, residuals = 0.116631 and reduce chi-square, χ ² = 0.00111156. In conclusion, SFBD was found to be a suitable and efficient method in drying of pepper and may be used for continuous drying processes.